2017
DOI: 10.18632/oncotarget.23583
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of antibody-inducing immunogens in tumor tissue identifies PSMA1, LAP3, ANXA3, and maspin as colon cancer markers

Abstract: We hypothesized that cancer tissue immunogens – antigens capable of inducing specific antibody production in patients – are promising targets for development of precision diagnostics and humoral immunotherapies. We developed an innovative immuno-proteomic strategy and identified new immunogenic markers of colon cancer. Proteins from cancers and matched normal tissues were separated by 2D gel electrophoresis and blotted with serum antibodies from the same patients. Antibody-reactive proteins were seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 38 publications
(41 reference statements)
1
36
0
Order By: Relevance
“…Furthermore, 45 prognosis-related features were obtained through the analysis of PPI networks and mapped into multiple cancer-related pathways. Among them, some prognosis-related features were directly related with the occurrence, development or prognosis of cancer, such as PSMA1 (degree = 54) was identified as colon cancer markers by proteomic profiling (Yang et al, 2018), FGFR3 (degree = 37) was related with multi-regional colon cancer through inter-and intra-tumor profiling (Kogita et al, 2015), ALPi is selectively induced by HDACi in colon cancer cells in a KLF5 (degree = 13) dependent manner (Shin et al, 2014), GLS2 (degree = 10) was validated as differential expression gene in colon cancer cells (Alix-Panabieres et al, 2017) and LEP (degree = 10) was examined to be associated with the development of colorectal cancer (Rezaei-Tavirani et al, 2013). Furthermore, several pathways were provided to be colon cancer-related pathways, such as wnt pathway, PI3K-AKT signaling pathway and cell cycle signaling pathway were reported as common oncogenic signaling pathways (Sanchez-Vega et al, 2018), which could be regulated by PSMA1 (degree = 54), MRAS (degree = 10), and LEP (degree = 10), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 45 prognosis-related features were obtained through the analysis of PPI networks and mapped into multiple cancer-related pathways. Among them, some prognosis-related features were directly related with the occurrence, development or prognosis of cancer, such as PSMA1 (degree = 54) was identified as colon cancer markers by proteomic profiling (Yang et al, 2018), FGFR3 (degree = 37) was related with multi-regional colon cancer through inter-and intra-tumor profiling (Kogita et al, 2015), ALPi is selectively induced by HDACi in colon cancer cells in a KLF5 (degree = 13) dependent manner (Shin et al, 2014), GLS2 (degree = 10) was validated as differential expression gene in colon cancer cells (Alix-Panabieres et al, 2017) and LEP (degree = 10) was examined to be associated with the development of colorectal cancer (Rezaei-Tavirani et al, 2013). Furthermore, several pathways were provided to be colon cancer-related pathways, such as wnt pathway, PI3K-AKT signaling pathway and cell cycle signaling pathway were reported as common oncogenic signaling pathways (Sanchez-Vega et al, 2018), which could be regulated by PSMA1 (degree = 54), MRAS (degree = 10), and LEP (degree = 10), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that ANXA3 plays an important role in tumor growth and progression. Clinical evidence indicates that ANXA3 could be a potential biomarker of several types of cancers, such as bladder cancer, colon cancer and gastric cancer . It can also serve as an important marker for the invasion, the metastasis and the prognosis of breast cancer…”
Section: Discussionmentioning
confidence: 99%
“…To better characterize and stratify cancer at the molecular level, we have embarked on an intense effort to identify molecular biomarkers of colorectal and other cancers with the goal of developing more efficient risk stratification for cancer diagnosis and treatment [11][12][13][14]. By deep proteome profiling of CRC by mass spectrometry, we observed that the protein STAT1 is upregulated in a subset of CRCs.…”
Section: Introductionmentioning
confidence: 99%